Nanopartículas de prata e Ag/Zno nanoestruturado como agentes antimicrobianos obtidos por processo hidrotermal de micro-ondas. - Santana, Suelanio Viegas de (2012)
This study consists of the acquisition, characterization and evaluation of antimicrobial silver nanoparticles and nanostructured Ag/ZnO. The silver nanoparticles were obtained through a new route using AgNO3 as precursor salt and ammonium citrate as reducing agent. Concerning the commercial zinc oxide, silver nanoparticles were impregnated using the microwave hydrothermal method at different synthesis times. Samples of Ag / ZnO nanostructured were characterized by using techniques of X-Ray Diffraction (DRX), Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). The colloidal silver nanoparticles obtained during the processes were characterized through optical spectroscopy in the ultraviolet and visible (UV-Vis) regions. Antimicrobial activity assays were carried for the Ag / ZnO nanostructured and for colloidal silver nanoparticles. They were included six bacteria species as well as six fungal species. Analysis of toxic and cytotoxic activity was performed for colloidal silver nanoparticles on fingerlings of Poecilia Reticulata and Artemia salina. The results show that the chosen synthesis method is effective for silver synthesis, as well as for the process of impregnation of the silver nanoparticles on the commercial zinc oxide. The biological tests revealed significant antimicrobial activity of silver nanoparticles on the micro-organisms analyzed and their low toxicity.